2018
DOI: 10.2478/fiqf-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit Tool for Minimizing the Risk of Fraud

Abstract: The purpose of the article is to analyze the relevance of the audit in minimizing the risk of fraud. The methodology of the research: literature analysis, internal audit research and questionnaires for the selected group of companies were carried out for the purpose of the article. The result: internal audit of micro-enterprises is implemented sporadically, so it is difficult to talk about its effectiveness, while in other entities it fulfills its role, provided it is properly carried out, which means while ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Apabila fraud tidak terdeteksi, artinya Auditor Internal tidak mengantisipasi fraud dengan melakukan jenis pengujian tertentu (Bishop, 2004). Oleh karena itu, Auditor Internal dituntut memiliki kompetensi sebagai kemampuan individu untuk melakukan pekerjaan atau tugas yang meliputi seperangkat pengetahuan, keterampilan, dan perilaku yang ditentukan oleh profesi tertentu (Klamut, 2018). Lee (2009) berpendapat bahwa hasil audit harus independen, objektif, dan dapat dipertanggungjawabkan sehingga memberikan tingkat assurance yang tinggi bagi manajemen organisasi sebagai pemakai informasi laporan internal agar keputusan yang diambil tepat sasaran.…”
Section: Pembahasan Analisis Terhadap Perspektif Teori Kompetensiunclassified
“…Apabila fraud tidak terdeteksi, artinya Auditor Internal tidak mengantisipasi fraud dengan melakukan jenis pengujian tertentu (Bishop, 2004). Oleh karena itu, Auditor Internal dituntut memiliki kompetensi sebagai kemampuan individu untuk melakukan pekerjaan atau tugas yang meliputi seperangkat pengetahuan, keterampilan, dan perilaku yang ditentukan oleh profesi tertentu (Klamut, 2018). Lee (2009) berpendapat bahwa hasil audit harus independen, objektif, dan dapat dipertanggungjawabkan sehingga memberikan tingkat assurance yang tinggi bagi manajemen organisasi sebagai pemakai informasi laporan internal agar keputusan yang diambil tepat sasaran.…”
Section: Pembahasan Analisis Terhadap Perspektif Teori Kompetensiunclassified
“…Also, they focused on the implementation of risk-based internal audit (RBIA) approach into practice. Klamut (2018) analyzed the effect of internal audit on minimizing the risk of fraud. Research results indicated that internal audit of small firms is implemented sporadically, so it is difficult to talk about its effectiveness, while on other size entities internal audit fulfills its role, provided that is properly carried out.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Menurut Klamut (2018), kompetensi pengendalian internal sangat diperlukan dalam usaha mencegah dan mendeteksi fraud. Namun terkadang, auditor internal gagal memenuhi beberapa kompetensi penting dari fraud karena mereka hanya menghadapi kasus fraud yang kebetulan terjadi di organisasi (Đorđević & Đukić, 2015;Hassink et al, 2010).…”
unclassified